Brachytherapy quality assurance in the PORTEC-4a trial for molecular-integrated risk profile guided adjuvant treatment of endometrial cancer. (February 2021) - Wortman, B.G.; Astreinidou, E.; Laman, M.S.; van der Steen-Banasik, E.M.; Lutgens, L.C.H.W.; Westerveld, H.; Koppe, F.; Slot, A.; van den Berg, H.A.; Nowee, M.E.; Bijmolt, S.; Stam, T.C.; et al.
Highlights: Quality assurance is essential for uniform treatment in multi-institutional radiotherapy trials. At dummy run, 71.4% of the brachytherapy plans needed revisions to fulfil trial protocol requirements. At annual QA, 18.5% of the reviewed brachytherapy plans showed major protocol deviations. Annual QA contributes to protocol compliance, ensuring high-quality VBT. Abstract: Objective: The PORTEC-4a trial investigates molecular-integrated risk profile guided adjuvant treatment for endometrial cancer. The quality assurance programme included a dummy run for vaginal brachytherapy prior to site activation, and annual quality assurance to verify protocol adherence. Aims of this study were to evaluate vaginal brachytherapy quality and protocol adherence. Methods: For the dummy run, institutes were invited to create a brachytherapy plan on a provided CT-scan with the applicator in situ. For annual quality assurance, institutes provided data of one randomly selected brachytherapy case. A brachytherapy panel reviewed and scored the brachytherapy plans according to a checklist. Results: At the dummy run, 15 out of 21 (71.4%) institutes needed adjustments of delineation or planning. After adjustments, the mean dose at the vaginal apex (protocol: 100%; 7 Gy) decreased from 100.7% to 99.9% and range and standard deviation (SD) narrowed from 83.6–135.1 to 96.4–101.4 and 8.8 to 1.1, respectively. At annual quality assurance, 22 out of 27 (81.5%) cases had no or minor and 5 out of 27 (18.5%) major deviations. Most deviations were related to delineation, mean dose at the vaginal apex (98.0%, 74.7–114.2, SD 7.6) or reference volume length. Conclusions: Most feedback during the brachytherapy quality assurance procedure of the PORTEC-4a trial was related to delineation, dose at the vaginal apex and the reference volume length. Annual quality assurance is essential to promote protocol compliance, ensuring high quality vaginal brachytherapy in all participating institutes.